The Effect Of Education And Training On Teacher Performance At SMA Negeri 3 Banjarbaru - Aulia Rahmi; Abdul Kadir; Fredy Jayen; Rifqi Amrulloh (Jurnal Ekonomi, 2024)
The aim of this research is to determine and analyze the influence of education and training simultaneously and partially on teacher performance at SMANegeri3 Banjarbaru. In this research, a descriptive design with a quantitative approach was used. The population in this research was the principal and teachers at SMANegeri 3 Banjarbaru as many as 62 people. The sampling technique used by the author is non-propability, namely using saturated sampling, that is, all members of the population totaling 62 people are used as samples. Data analysis is carried out based on primary data obtained directly through distributing questionnaires to patients, which will then be analyzed using multiple regression analysis with the help of the SPSS (Statistical Product and Service Solution) Version 26 program. for Windows. Data collection techniques use literature study, observation, interviews, documentation and questionnaires, then the data uses multiple regression analysis. To test the hypothesis, use the t test (partial) and F test (simultaneous). The results of the research explain that education and training simultaneously and partially have a significant effect on teacher performance at SMA Negeri 3 Banjarbaru. Training is a variable that has a dominant influence on teacher performance at SMA Negeri 3 Banjarbaru. The influence of education and training variables on teacher performance is 53.6%